Serological survey of Neospora caninum in small ruminants from Pernambuco State, Brazil - Tembue, Antonio Amélia Santos Mucalane; Ramos, Rafael Antonio de Nascimento; Sousa, Thais Rabelo de [UNESP]; Albuquerque, Alessandra Ribeiro; Costa, Alvimar José da [UNESP]; Meunier, Isabelle Maria Jaqueline; Faustino, Maria Aparecida da Gloria; Alves, Leucio Câmara (Colégio Brasileiro de Parasitologia Veterinária, 2011)
A infecção por Neospora caninum é uma importante causa de abortos em bovinos, assim como mortalidade neonatal em caprinos e ovinos. Uma pesquisa sorológica de anticorpos anti-N. caninum foi realizada no município de Ibimirim (PE, Brasil). Os resultados ao teste de imunofluorescência revelaram que 26,6% (85/319) dos caprinos e 64,2% (52/81) dos ovinos foram positivos. A reatividade à sorologia foi associada com a idade nos caprinos (p < 0,01) e ovinos (p > 0,05), com maior ocorrência nos animais mais velhos. Estes resultados indicam exposição a N. caninum entre pequenos ruminantes na área estudada.

Neospora caninum infection is an important cause of bovine abortion as well as neonatal mortality in goats and sheep. A serological survey for antibodies against N. caninum in goats and sheep was carried out in the municipality of Ibimirim, PE, Northeastern Brazil. The imunnofluoresce antibody test showed that 26.6% (85/319) of the goats and 64.2% (52/81) of the sheep were positive. Serologic reactivity was associated with age in goats (p < 0.01) and sheep (p > 0.05), with increasing rates in older animals. These results indicate exposure to N. caninum among small ruminants in the study area.
Inquérito sorológico de Neospora caninum em pequenos ruminantes do estado de Pernambuco, Brasil
Keywords: Coccidiosis; Small ruminants; Serology; Coccidiose; Pequenos ruminantes; Sorologia